Implementasi Peraturan Daerah Nomor 1 Tahun 2019 Tentang Retribusi Jasa Umum Dalam Pengelolaan Retribusi Pasar Di Pasar Raya Padang - Fresha Atmuria; Afriva Khaidir (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2020)
The aim of this study was to analyse the implementation of regional regulations No 1 of 2019 on Retribusi Jasa Umum dalam Pengelolaan Retribusi pasar di Pasar Raya Padang. Background of this study is because several problems were found in market retribution of Pasar Raya Padang that is, a collection that does not give a ticket or evidence of payment of retribution. Limited market management capabilities to provide a place, there are still traders who do not pay retribution. As well as a lack of oversight from Padang city trade service. Formulation of the problem in this study is how the implementation of regional regulations No 1 of 2019 on Retribusi Jasa Umum dalam Pengelolaan Retribusi pasar di pasar Raya Padang. What are the constraints in the implementation of regional regulations. This study was qualitative with descriptive method. Selection of informants was done with Purposive for decided key informants and next decided with SnowballSampling technique. This observation data collection techniques was interview and documentation study. For data analysis was done by data collection, data reduction, presentation of data, and conclusions. Then the validity of this data is tested by Triangulasi Sumber which is then analysed with data analysis techniques. Measurement toward the implementation of regional regulations No 1 of 2019. The researcher used measure of policy implementation according George C. Edward III, there are four policy implementation indicators such as, communication, resource, disposition, and bureaucratic structure. This study reveal that implementation of the collection of market retribution was carried out by Dinas Perdagangan Kota Padang to traders who sell in Pasar Raya Padang. Based on findings and discussion The Implementation of Regional Regulations No 1 of 2019 on Retribusi Jasa Umum dalam Pengelolaan Retribusi Pasar di Pasar Raya Padang was influenced by communication, resource and attitudes of the bureaucracy and implementers. Constraints faced in the implementation of the management of market retribution in Pasar Raya Padang is less awareness of traders in paying market retribution, so that many causes arrears on market retribution and the target was not achieved.